2017
DOI: 10.3892/ol.2017.7703
|View full text |Cite
|
Sign up to set email alerts
|

Glucagonoma and the glucagonoma syndrome (Review)

Abstract: Abstract. Glucagonoma is an extremely rare pancreatic α-islet cell tumor and is often accompanied by certain clinical symptoms including necrotizing migratory erythema (NME), diabetes, weight loss and anemia. The objectives of the current review were to discern the clinical features, diagnosis, treatment and prognosis of glucagonoma by evaluating 623 reported cases. A 1998 study reviewed 407 cases and 216 cases were reported in studies published after 1998. The current review consisted of 268 males and 339 fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 37 publications
(41 reference statements)
0
57
0
1
Order By: Relevance
“…The treatment of choice for glucagonoma is surgery given the poor response to chemotherapy. In cases of early diagnosis, surgical resection could be curative (6)(7)(8). The morbidity of GS is mostly due to NME, which, as it did in our case, frequently produces extensive lesions that affect the quality of life of the patient.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…The treatment of choice for glucagonoma is surgery given the poor response to chemotherapy. In cases of early diagnosis, surgical resection could be curative (6)(7)(8). The morbidity of GS is mostly due to NME, which, as it did in our case, frequently produces extensive lesions that affect the quality of life of the patient.…”
Section: Discussionmentioning
confidence: 51%
“…NME is the most characteristic clinical manifestation of the disease and is present in up to 70% of cases (4,6,8,9). Often, as in this case, NME is the first manifestation of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study published in 2018 on 623 cases of glucagonoma revealed a mean age of 52.4 years and men to women ratio of 0.79 (27). Their presentation included most frequently NME of 82%, followed by diabetes mellitus 68%, weight loss 60%, anaemia in almost half of the subjects, and glositis/stomatitis/cheilitis of 41% (27).…”
Section: Glucagonoma-associated Skin Lesionsmentioning
confidence: 99%
“…A study published in 2018 on 623 cases of glucagonoma revealed a mean age of 52.4 years and men to women ratio of 0.79 (27). Their presentation included most frequently NME of 82%, followed by diabetes mellitus 68%, weight loss 60%, anaemia in almost half of the subjects, and glositis/stomatitis/cheilitis of 41% (27). Almost two thirds of the glucagonomas were located at pancreas tail while a mean tumour diameter was 5 cm, and almost half of the patients had liver metastasis at first diagnosis (especially in older persons) (27).…”
Section: Glucagonoma-associated Skin Lesionsmentioning
confidence: 99%